Long noncoding RNA H19 promotes vincristine resistance in multiple myeloma by targeting Akt - Wang, Yigang; Xu, Shijuan; Wang, Lu; Liu, Juanni; Wang, Juan; Zhou, Jun (Cellular and Molecular Biology, 2020)
Multiple myeloma is a malignant proliferation of plasma cells that results from a single clone. Manifestations include bone pain or fractures, kidney failure, susceptibility to infection, anemia, and hypercalcemia. To investigate the relationship between vincristine (VCR) resistance and Long noncoding RNA H19 (Lnc-RNA H19) in multiple myeloma (MM) this experiment was set up. For this aim, RT-PCR was used to detect the expression of lnc-RNA H19 in 60 MM patients from No.215 Hospital of Shaanxi Nuclear Industry and 50 healthy controls, and further detected the expression of related genes in myeloma cell lines and VCR myeloma resistant strains. MTT assay, flow cytometry assay, western-blotting assay and luciferase assay were used to analyze the growth, apoptosis and protein phosphorylation levels of drug-resistant RPMI 8226/VCR and RPMI 8226 cells after VCR treatment and plasmid transprinting. Results showed that the relative expression of lnc-RNA H19 was significantly increased in MM patients and drug-resistant strains RPMI 8226-VCR (****p<0.0001), while apoptosis of various MM cell lines increased after VCR treatment, while apoptosis of RPMI 8226-VCR was significantly decreased (***p<0.001). Lnc-RNA H19 overexpression plasmid pcdna3.1-h19 and Akt overexpression plasmid pcdna3.1-akt decreased apoptosis in RPMI 8226 cell lines without VCR resistance (***p<0.001), while the recombination of siRNA-h19 and siRNA-akt plasmid increased apoptosis in RPMI 8226-VCR (***p<0.001). The lnc-RNA H19/Akt pathway is closely related to the occurrence of VCR resistance in MM cells, and the down-regulation of H19 can significantly improve the sensitivity of VCR in MM.